Implementasi Penggunaan Uang Paksa (Dwangsom) Terhadap Putusan Hakim (Studi Kasus Pengadilan Agama Denpasar) - Dina Amalia; Nyoman Sugiartha; Ketut Adi Wirawan (Jurnal Analogi Hukum, 2024)
Dwangsom is defined as an additional penalty imposed by the judge on the defendant (convicted) to pay a sum of money to the plaintiff with the aim that the defendant (convicted) is willing to fulfill the main sentence imposed by the judge voluntarily within a predetermined time. The problem formulations raised in this paper are (1) How is the application of dwangsom to the judge's decision at the Denpasar Religious Court, and (2) How are the obstacles to the application of dwangsom to defendants who are unable to carry out the decision (economic incapacity). The research method used is an empirical research method. Forced money is regulated in 606a BRV and 606b BRV, in its application forced money in Indonesia has been applied properly according to the Law on the application of forced money (dwangsom), although forced money has been implemented properly but there are still some technical obstacles, which need to be resolved.